Clinical reappraisal of the Composite International Diagnostic Interview Screening Scales (CIDI‐SC) in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS). Issue 4 (December 2013) - Kessler, Ronald C.; Santiago, Patcho N.; Colpe, Lisa J.; Dempsey, Catherine L.; First, Michael B.; Heeringa, Steven G.; Stein, Murray B.; Fullerton, Carol S.; Gruber, Michael J.; Naifeh, James A.; Nock, Matthew K.; Sampson, Nancy A.; et al.
Abstract A clinical reappraisal study was carried out in conjunction with the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) All‐Army Study (AAS) to evaluate concordance of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) diagnoses based on the Composite International Diagnostic Interview Screening Scales (CIDI‐SC) and post‐traumatic stress disorder (PTSD) checklist (PCL) with diagnoses based on independent clinical reappraisal interviews (Structured Clinical Interview for DSM‐IV [SCID]). Diagnoses included: lifetime mania/hypomania, panic disorder, and intermittent explosive disorder; six‐month adult attention‐deficit/hyperactivity disorder; and 30‐day major depressive episode, generalized anxiety disorder, PTSD, and substance (alcohol or drug) use disorder (abuse or dependence). The sample (n = 460) was weighted for over‐sampling CIDI‐SC/PCL screened positives. Diagnostic thresholds were set to equalize false positives and false negatives. Good individual‐level concordance was found between CIDI‐SC/PCL and SCID diagnoses at these thresholds (area under curve [AUC] = 0.69–0.79). AUC was considerably higher for continuous than dichotomous screening scale scores (AUC = 0.80–0.90), arguing for substantive analyses using not only dichotomous case designations but also continuous measures of predicted probabilities of clinical diagnoses. Copyright © 2013 John Wiley & Sons, Ltd.